ECONOMIC VIABILITY OF CATFISH FARMING IN MOKWA, MOKWA LOCAL GOVERNMENT AREA, NIGER STATE, NIGERIA - ABDULLAHI , U.U; IPINJULO, J.K; LAWAL, A.F; HAUWA, J; MAIRO, A. (Nigerian Journal of Fisheries, 2019)
Fish farming is becoming one of the areas of employment and source of income. There is need to establish the economic viability of catfish farming in Mokwa-township, for proper advice to prospective investors. The fish farms in Mokwa Township were enumerated in a farm management survey. Simple random sampling technique were used to select seven of the catfish farms from fifteen catfish farm in the study area. There were observed from the beginning to the end of production in a cost-rout approach for two production period. The Gross margin analysis, profitability ratios and multiple regression analysis were used to analysis the result. The result showed that feed input accounted for 80 percent of the total cost of production while fingerlings accounted for 8.6 percentage, labour and medication account for 10 and 1.1 percent. The total variable cost was N340, 475, feed, fingerlings, and labour accounted for N273, 782, N29143, N34, 071 respectively. The gross revenue was N461, 643 and the gross margin was N121, 168. The net profit margin of 26.06 percent. Based on the result of this study, catfish farming is viable and profitable in the study area. It is therefore recommended for prospective investors.